Conversion of a Fleeting Open‐Shell Iron Nitride into an Iron Nitrosyl. (21st October 2019) - Chang, Hao‐Ching; Lin, Yen‐Hao; Werlé, Christophe; Neese, Frank; Lee, Way‐Zen; Bill, Eckhard; Ye, Shengfa
Abstract: Terminal metal nitrides have been proposed as key intermediates in a series of pivotal chemical transformations. However, exploring the chemical activity of transient tetragonal iron(V) nitrides is largely impeded by their facile dimerization in fluid solutions. Herein, in situ EPR and Mössbauer investigations are presented of unprecedented oxygenation of a paramagnetic iron(V) nitrido intermediate, [Fe V N(cyclam‐ac)] + (2, cyclam‐ac − =1, 4, 8, 11‐tetraazacyclotetradecane‐1‐acetate anion), yielding an iron nitrosyl complex, [Fe(NO)(cyclam‐ac)] + (3 ). Further theoretical studies suggest that during the reaction a closed‐shell singlet O atom is transferred to 2 . Consequently, the N−O bond formation does not follow a radical coupling mechanism proposed for the N−N bond formation but is accomplished by three mutual electron‐transfer pathways between 2 and the O atom donor, thanks to the ambiphilic nature of 2 . Abstract : Offen für Veränderung : In‐situ‐ESR‐ und Mößbauer‐Studien zeigen die zuvor unbekannte Oxygenierung eines kurzlebigen paramagnetischen Eisen(V)‐nitrid‐Intermediats unter Bildung einer Nitrosyleisenspezies. Rechnungen zufolge umfasst die N‐O‐Bindungsbildung den Transfer eines formal geschlossenschaligen Singulett‐O‐Atoms zum (FeN) 2+ ‐Kern einhergehend mit synergetischen Orbitalwechselwirkungen.